Antinatriuretic phenomena seen in children with acute pyelonephritis may be related to the activation of intrarenal RAAS - Lee, Jun Ho (Medicine (Baltimore), 2018)
We investigated whether antinatriuretic phenomena [decreases in urinary sodium (uNa) and fractional excretion of sodium (FENa)] seen in children with acute pyelonephritis (APN) are associated with the renin–angiotensin–aldosterone system (RAAS). We examined 114 children experiencing their first episode of febrile urinary tract infection (fUTI) consecutively admitted to our hospital from July 2012 to June 2014. Blood tests [C-reactive protein, white blood cell count, erythrocyte sedimentation rate, and aldosterone (Aldo)] and urine tests [uNa, urine potassium (uK) and FENa] were performed upon admission. All enrolled children underwent a 99m-dimercaptosuccinic acid renal scanning (DMSA) at admission. Areas with cortical defects (AreaCD) and uptake counts (UptakeCD) on their DMSA scans were calculated. Data were compared between children with positive DMSA results (APN), lower urinary tract infection (L-UTI), and controls; and between children with high and low Aldo levels. uNa, uNa/K, and FENa negatively correlated with AreaCD%, UptakeCD, and Aldo; were significantly lower in APN patients than in LUTIs and controls regardless of Aldo level; were lower in the high Aldo group than in the low Aldo group. However, there is no difference in AreaCD% and UptakeCD between APN children with the high and low Aldo level. Decreases in uNa, uNa/K, and FENa in children with APN may result from an antinatriuretic effect of RAAS and be related to the activation of the intrarenal RAAS.